On the Need to Use Smart Contracts in Enterprise Application Integration - Parahyba, Fernando; Dornelles, Eldair F.; Roos-Frantz, Fabrícia; Frantz, Rafael Z.; Molina-Jiménez, Carlos; Reina Quintero, Antonia M.; Bocanegra, José; Sawicki, Sandro (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2022: Anais do XXV Congresso Ibero-Americano em Engenharia de SoftwareDO - 10.5753/cibse.2022.20973, 2022)
Integration processes involve Business Constraints and Service Level Agreements that, with current technology, are not monitored or enforced automatically at run-time. This approach leaves the participants with no means of supervising the development of their interactions or of collecting indisputable evidence to ease the resolution of disputes that can potentially emerge. In this paper, to address the issue, we suggest the inclusion of smart contracts in integration processes to supervise and mediate, at run-time, the agreements to which the participants commit. We discuss the requirements that smart contracts for integration processes need to meet and the challenges involved in writing, executing, deploying, and verifying them.